Study of thermoelastoplastic contact deformation of production tooling mixed structures - Bondar, S. V.; Lavinsky, D. V. (Kluwer Academic/Plenum Publishers, 2011)
A calculation technique based on the unified methodological approach is proposed for the analysis of thermoelastoplastic contact deformation of mixed structures. The proposed numerical technique involves the finite element method. The problem of stress-strain state evaluation for one class of mixed shrouded half-hot extrusion dies is considered. Recommendations on production tooling design are given
Keywords: thermoelastoplastic deformation; contact interaction; strength; stiffness; finite element method; heat transfer; mixed shrouded extrusion die